Question:

Find \( A^{-1} \), if \[ A = \begin{pmatrix} 1 & 2 & 1 \\ 2 & 3 & -1 \\ 1 & 0 & 1 \end{pmatrix} \] Hence, solve the following system of equations: \[ x + 2y + z = 5 \\ 2x + 3y = 1 \\ x - y + z = 8 \]

Show Hint

When solving systems of linear equations, finding the inverse of the coefficient matrix allows you to solve for the variable matrix. The inverse is calculated using the adjugate and determinant.
Hide Solution
collegedunia
Verified By Collegedunia

Solution and Explanation

Step 1: The given integral can be written as: \[ I = \int e^x \left( \frac{x}{\sqrt{1+x^2}} + \frac{1}{(1+x^2)^{\frac{3}{2}}} \right) dx \] Let: \[ f(x) = \frac{x}{\sqrt{1+x^2}} \] Step 2: Now, calculate the derivative of \( f(x) \): \[ f'(x) = \frac{\sqrt{1+x^2} - \frac{x \cdot x}{\sqrt{1+x^2}}}{1+x^2} = \frac{\sqrt{1+x^2} - \frac{x^2}{\sqrt{1+x^2}}}{1+x^2} \] Simplify the numerator: \[ f'(x) = \frac{\sqrt{1+x^2} - \frac{x^2}{\sqrt{1+x^2}}}{1+x^2} = \frac{1}{(1+x^2)^{\frac{3}{2}}} \] Thus, the integral becomes: \[ I = \int e^x \left( f(x) + f'(x) \right) dx \] Step 3: Using the standard result: \[ \int e^x \left( f(x) + f'(x) \right) dx = e^x f(x) + C \] Substitute \( f(x) = \frac{x}{\sqrt{1+x^2}} \): \[ I = e^x \frac{x}{\sqrt{1+x^2}} + C \] Final Answer: \[ \boxed{I = e^x \frac{x}{\sqrt{1+x^2}} + C} \] Explanation: 1. Splitting the Integral: The given integral is split into terms containing \( \frac{x}{\sqrt{1+x^2}} \) and \( \frac{1}{(1+x^2)^{\frac{3}{2}}} \). 2. Defining \( f(x) \): The function \( f(x) \) is chosen as \( \frac{x}{\sqrt{1+x^2}} \) because its derivative results in the second term, \( \frac{1}{(1+x^2)^{\frac{3}{2}}} \). 3. Applying the Formula: The integral formula for \( \int e^x (f(x) + f'(x)) dx = e^x f(x) + C \) is directly applied. 4. Substitution: Finally, substituting \( f(x) \) into the formula gives the result.
Was this answer helpful?
0
0

Questions Asked in CBSE CLASS XII exam

View More Questions